Unsticking the centre-piece : the liberation of European copyright law? - Griffiths, Jonathan (Journal of Intellectual Property, Information Technology and Electronic Commerce Law, ISSN 2190-3387, 2010)
Following European legislative initiatives in the field of copyright limitations and exceptions, policy flexibilities formerly available to mem- ber states has been greatly diminished. The law in this area is increasingly incapable of accommodating any expansion in the scope of freely permitted acts, even where such expansion may be an appropriate response to changes in social and technological conditions. In this article, the causes of this problem are briefly canvassed and a number of potential solutions are noted. It is suggested that one such solution the adoption of an open, factor-based model similar to s 107 of the United States Copyright Act has not received the serious attention it deserves. The fair use paradigm has generally been dismissed as excessively unpredictable, contrary to international law and/or culturally alien. Drawing on recent fair use scholarship, it is argued here that these disadvantages are over-stated and that the potential for the development of a European fair use model merits investigation.
Keywords: TEKIJÄNOIKEUS; POIKKEUSLUVAT; RAJOITUKSET; KOLMIVAIHETESTI; FAIR USE